Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Nanoscale particles for polymer degradation and stabilization-trends and future perspectives - Kumar, Annamalai Pratheep; Depan, Dilip; Tomer, Namrata Singh; Singh, Raj Pal (Progress in Polymer Science, 2009)
The field of nanoscience and nanotechnology is extending the applications of physics, chemistry, biology, engineering and technology into previously unapproached infinitesimal length scales. The polymer-nanoparticles/nanocomposites have been the exponentially growing field of research for developing the materials in last few decades and have been mainly focusing on the structure-property relationships and their development. Since the polymer-nanocomposites have been the staple of modern polymer industry, their durability under various environmental conditions and degradability after their service life are also essential fields of research. Thus, this article is intended to review the status of worldwide research in this aspect. Among various nanoparticulates, clay minerals and carbon nanotubes are more often used in enhancing physical, mechanical and thermal properties of polymers. In very few systems, the nano particulates have been incorporated into polymer as `nano-additives' for both purposes: degradation and stabilization of polymers. The degradation and durability of polymers is reviewed in the presence of nanoparticles/nanocomposites under different environmental conditions. Nanoparticle-induced biodegradation of polymers is also discussed. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanotubes; clay; Degradation and stabilization; Nanocomposites; Nanoparticles; Polymer